Takotsubo Syndrome Associated With Osimertinib In A Patient With Non-Small Cell Lung Cancer: A Case Report - Osorio, Álvaro; López, Valeria; Hidalgo, Alejandra; García, Enrique (Revista Colombiana de Hematología y Oncología, 2023)
Osimertinib is a mono-anilino-pyrimidine compound that specifically binds to the EGFR kinase domain irreversibly by targeting the cysteine-797 residue in the ATP binding site via covalent bond formation. In 2018 osimertinib was approved by the US food and drug administration (FDA) For the first-line treatment of patients with metastatic non-small cell lung cancer (NSCLC) whose tumors have EGFR exon 19 deletions or exon 21 L858R mutations. In the phase III FLAURA trial, 556 patients with treatment-naïve, egfr-mutated advanced nsclc were randomly assigned to osimertinib versus standard of care EGFR TKI (Gefitinib or Erlotinib). Osimertinib showed superior efficacy in the first-line treatment of EGFR mutation–positive advanced NSCLC, with a similar safety profile and lower rates of serious adverse events. on regard to tolerability, the trial.